2020
DOI: 10.1186/s12935-020-1126-1
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted roles of long noncoding RNAs in pancreatic cancer: an update on what we know

Abstract: Pancreatic cancer (PC) is one of the leading causes of cancer-related deaths worldwide. Due to the shortage of effective biomarkers for predicting survival and diagnosing PC, the underlying mechanism is still intensively investigated but poorly understood. Long noncoding RNAs (lncRNAs) provide biological functional diversity and complexity in protein regulatory networks. Scientific studies have revealed the emerging functions and regulatory roles of lncRNAs in PC behaviors. It is worth noting that some in-dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 94 publications
0
16
0
Order By: Relevance
“…The lack of effective methods for early PC detection is a prime reason for the poor survival rate. As of today, lncRNAs have been exploited as the biomarkers for the clinical diagnosis and treatment of various cancers, including PC [ 58 , 59 ]. One such circulatory lncRNA is ABHD11-AS1, which was recently studied for its significance in PC progression, diagnosis, and treatment [ 24 , 25 , 26 ].…”
Section: Oncogenic Role Of Abhd11-as1 Lncrna In Human Cancersmentioning
confidence: 99%
“…The lack of effective methods for early PC detection is a prime reason for the poor survival rate. As of today, lncRNAs have been exploited as the biomarkers for the clinical diagnosis and treatment of various cancers, including PC [ 58 , 59 ]. One such circulatory lncRNA is ABHD11-AS1, which was recently studied for its significance in PC progression, diagnosis, and treatment [ 24 , 25 , 26 ].…”
Section: Oncogenic Role Of Abhd11-as1 Lncrna In Human Cancersmentioning
confidence: 99%
“…Reprograming of the translation machinery in cancer cells is important function of the key oncogenic signalings, promoting cellular transformation. Increased activity of translational machinery has been shown to be critical in many cancer cells, including breast [ 97 ], pancreatic [ 98 ], liver [ 99 ], and colorectal cancer [ 100 ], and leukemia [ 101 ]. Thus, lncRNA-mediated regulation of protein translation plays an important role in promoting oncogenic signaling, and specific targeting of these lncRNAs holds promise for developing highly targeted therapies in cancer and other human diseases.…”
Section: Acting Mechanisms Of Lncrnas In the Regulation Of Translamentioning
confidence: 99%
“…In the past decades, accumulating evidence showed that lncRNAs exert an important effect on the processes of transcriptional regulation, post-transcriptional regulation, and epigenetic modification [ 7 ]. The dysregulation of lncRNAs has been well documented in the tumorigenesis and development of human malignancies [ 8 , 9 ]. For example, enhanced lncRNA ARSR expression was shown in RCC‐initiating cells, related with dismal survival, and contributed to the sunitinib resistance in RCC patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%